1996
DOI: 10.1021/ma951844j
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Spherical Micellar Systems of Styrene−Isoprene Diblock Copolymers. 2. Nonlinear Stress Relaxation Behavior

Abstract: Nonlinear stress relaxation after imposition of step strain γ (≤2) was examined for blends of styrene−isoprene (SI) diblock copolymers in a homopolyisoprene (hI) matrix. The blends contained spherical micelles with S cores and I corona. For most cases, the blends had no plasticity and exhibited complete relaxation. Fast and slow relaxation processes characterizing the linear viscoelastic behavior of the micelles (part 1) were observed also for nonlinear relaxation moduli G(t,γ). For sufficiently small γ, G(t,γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(106 citation statements)
references
References 12 publications
10
95
1
Order By: Relevance
“…Relaxation moduli were calculated via division of the time-dependent engineering stress by the magnitude of the jump strain in each experiment. This procedure to calculate the stress relaxation modulus is consistent with the methodology of Watanabe et al 29 Chen et al 41 suggest that true stress is more accurate than engineering stress, particularly in the nonlinear regime.…”
Section: Stress Relaxation Measurementssupporting
confidence: 70%
See 1 more Smart Citation
“…Relaxation moduli were calculated via division of the time-dependent engineering stress by the magnitude of the jump strain in each experiment. This procedure to calculate the stress relaxation modulus is consistent with the methodology of Watanabe et al 29 Chen et al 41 suggest that true stress is more accurate than engineering stress, particularly in the nonlinear regime.…”
Section: Stress Relaxation Measurementssupporting
confidence: 70%
“…Osaki et al 30 conclude that time-dependent reptation based on the tube model and time-and strain-dependent retraction along the tube axis are uncoupled below 700% strain, but the factorability of time and strain is not possible at higher strains. Watanabe et al 29 conclude that time-strain separability can be applied to styrene-isoprene diblock copolymers in the terminal relaxation regime, where terminal relaxation times are strain-independent below 200% strain. Ionic interactions in molten ionomers 28 do not invalidate the separability of time and strain.…”
Section: Stress Relaxationmentioning
confidence: 99%
“…9 does not pass through the origin, the Brownian response is given explicitly by the value of the curve there. This is much the same as with cessation experiments performed in a macroscopic rheometer [Watanabe et al (1996a[Watanabe et al ( , 1996b]. While it can be quite difficult to extract the Brownian microstructural response by direct imaging of particles, in this approach one need only make observations of the Lissajous-Bowditch curves.…”
Section: A Pipkin Diagram For Microrheologymentioning
confidence: 78%
“…A thorough review of traditional rheology techniques may be found in the work of Barnes et al (1989). Transient flows also give insight into the micromechanics of rate-dependent processes in steady-state flow behavior: Sudden removal of external forcing demonstrates that the microstructure relaxes over multiple time scales, each associated with distinct physical processes [Mackay and Kaffashi (1995); Watanabe et al (1996aWatanabe et al ( , 1996b; Kaffashi et al (1997); Foss (1999); Zia and Brady (2013)]. Such temporal response reveals the underlying connection between structure and rheology.…”
Section: Introductionmentioning
confidence: 99%
“…For example Mackay and Kaffashi (1995) and Kaffashi et al (1997) studied the decay of stress immediately after the cessation of imposed strain-rate on a sheared suspension; they found that the hydrodynamic stress decays instantaneously, as it must-the hydrodynamic stress is proportional to the imposed strain-rate, and thus must vanish in the absence of flow. Watanabe et al (1996b) and Watanabe et al (1996a) analyzed stress development and relaxation in sudden startup and cessation of shearing flow and found both short-and long-time relaxation modes. These studies show that the macroscopic stress relaxes via distinct transport processes, but the microstructural evolution that accompanies this relaxation is not as thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%